Analisis Mutu Layanan Peserta BPJS Kesehatan dengan Pendekatan Physical Environment Quality Dimension - Ruslang; Yanuar Azis, Anugerah; B, Khaeriah; Azizah, A. Nur; Mikhrunnisai, Andi; Mustafa, Idarwati; Ramlan, Pratiwi; Yakob, Asmirati; Nirmawati Darwis; Tetti Surianti (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2024)
This study analyses the quality of health services for BPJS Kesehatan participants with a focus on the physical environment dimension at Puskesmas Tanasitolo, Wajo District, South Sulawesi. The quality of the physical environment has a significant influence on patient satisfaction, which is an important element in the effectiveness of health services. A descriptive quantitative approach was used in this study. A total of 99 BPJS participants who met the criteria completed a questionnaire assessing various aspects of the physical environment, such as room conditions, design, and social factors. The analysis showed that the cleanliness and comfort of the facility, room arrangement, and adequacy of facilities and infrastructure significantly contributed to patient satisfaction. More than 80% of respondents were satisfied with the physical environment, especially in terms of room design and equipment condition. This finding is in line with previous studies showing that the physical environment plays an important role in the quality of healthcare services. Improving this aspect is crucial to increasing patient satisfaction. The physical environment has a significant influence on the satisfaction of BPJS participants at Puskesmas. Continuous improvement in this aspect is necessary to ensure optimal service.